Effects of aloe vera extracted on liver and kidney function changes induced by hydrogen peroxide in rats - Abdal, Tarik Abdulqadir; Haji, Aziza Raof; Markus, Melen Mansour (International Journal of Research in Medical Sciences, 2019)
Background: Aloe vera (Aloes) is a member of the Liliaceae family that is used as herbal medicine in many cultures for several purposes. The present study was designed to investigate the role of Aloe vera leaf gel extracts on lipid profiles and liver and kidney functions in rats. Methods: In this experimental investigation, a total of 20 healthy rats were divided into four following groups. Group I fed with normal diet and water. Group II administrated by 1% hydrogen peroxide with drinking water in a dark bottle prepared daily. Group III administrated with 5 ml of aloe vera oil added to 25 grams of their ratio for each rat (25 ml oil/125 g) also prepared daily with normal drinking water. Group IV also administrated with 5 ml of aloe vera oil added to 25 grams of their ratio with drinking water that contains 1% hydrogen peroxide in a dark bottle. The rats in all four groups fed for 21 days. Results: The subjects who were included in H2O2 had significantly higher concentrations of TG (146.79 vs. 73.09 mg/dL; p<0.001), cholesterol (123.60 vs. 68.90 mg/dL; p=0.001), and lower concentration of HDL (5.79 vs. 7.53 mg/dL; p<0.001) compared to the control group. While, the subjects in Aloe Vera group had lower concentration of cholesterol (55.90 vs. 68.90 mg/dL; p=0.004), and higher level of HDL (9.22 vs. 7.53 mg/dL; p<0.001). The subjects in the H2O2 had significantly higher concentrations of AST (76.64 vs. 30.04; p<0.001), ALT (64.94 vs. 23.38; p<0.001), urea (59.68 vs. 37.10; p=0.003), uric acid (0.92 vs. 0.59; p<0.001). Whereas, the subjects in Aloe Vera had substantially lower levels of AST (18.76 vs. 30.04; p=0.008). Conclusions: The present study showed that aloe vera gel extract is effective to improve the lipid profile and liver and kidney function.